New insights and possibilities in pharmacy education: Integration of new technologies and internationalization at home - Karatas, Sercin; Asik, Asuman; Curcic, Marijana; Durgo, Ksenija; Esteban, Javier; Cakmak, Gonca (Istanbul Journal of Pharmacy, 2025)
Pharmacy education is significantly transformed by active learning, ongoing development, and innovative educational approaches. The rapid advancement of technology, particularly the integration of artificial intelligence, is enhancing educational tools and methods. Additionally, the COVID-19 pandemic has highlighted the potential of virtual exchanges, making global education more accessible through internationalization at home. Both educators and students are adapting to these contemporary advancements, reshaping the education landscape. In pharmacy education, combining theoretical knowledge and practical skills is crucial for developing problem-solving, discussion, and critical thinking abilities. Problem-based learning is increasingly utilized as a novel educational method in this field. This paper explores new perspectives and possibilities in pharmacy education by presenting case studies that illustrate the application and benefits of problem-based learning and internationalization at home.